Quantitative Easing Policy Towards The National Revenue And Expediture Budget (APBN) In Crisis Period By The Central Bank - Dewantara, Reka; Pandansari, Rekyan (Faculty of Law, Andalas University, 2024)
After the abolition of the Emergency Financing Facility (FPD) by the 2016 Financial System Crisis Prevention and Management Law (PPKSK Law), there are potential problems that may arise if a bank applies for a Short-Term Liquidity Loan (PLJP) but in the process is unable to meet the requirements as stipulated in the Bank of Indonesia Regulation (PBI) on Short-Term Liquidity Loans (PLJP), or the Short-Term Liquidity Loan (PLJP) provided later fails to resolve the liquidity problems of the bank. The purpose of this article is to analyze the theoretical underpinnings of emergency liquidity assistance that have actually been covered in the previous Emergency Financing Facility (FPD) arrangement. The research method used is a normative juridical research (doctrinal research) type with an analytical approach and statutory approach. The results show that In crisis conditions, the government will need funding for the state budget at a low-interest rate, because if it has to seek from investors, the desired interest will be high and cannot be a solution in times of crisis. So it can be said that the financing needs of the state in times of crisis require BI because fiscal costs become cheaper, compared to having to seek from investors who ask for high returns. This funding model has been implemented in several developed countries with the term known as quantitative easing. With the open space for BI to carry out burden sharing in times of crisis continuously, it can trigger integrity risk or moral hazard.